2015
DOI: 10.1007/s11920-015-0617-6
|View full text |Cite
|
Sign up to set email alerts
|

Is Postpartum Depression a Distinct Disorder?

Abstract: The nosology of postpartum depression (PPD) is controversial. We review the evidence and arguments for and against the recognition of PPD as a distinct disorder and discuss the etiopathogenic and diagnostic validity of PPD as a distinct disorder, including its utility and indications for further research. Although multiple epidemiological and clinical studies have found that depression is more common following childbirth than at other times in a woman's life, there is conflicting evidence for the validity of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 39 publications
4
29
0
Order By: Relevance
“…The symptom profile of postpartum depression (PPD) (Glossary) includes sad mood, restlessness/agitation, and impaired concentration, thus resembling that of a major depressive disorder (MDD) experienced at other times in adulthood. PPD is often comorbid with anxiety [6,7], and is strongly predicted by a prepartum history of either depression or anxiety [2][3][4][5] (Box 1). While it is unclear whether PPD has any unique symptom characteristics [2,3], both postpartum anxiety and depression are obviously unique in their timing, some of their physiological and psychosocial risk factors (Box 2), and their consequences for the mother-infant dyad if not the entire family unit [4][5][6].…”
Section: Postpartum Anxiety and Depression Occur In At Least 1 In mentioning
confidence: 99%
See 1 more Smart Citation
“…The symptom profile of postpartum depression (PPD) (Glossary) includes sad mood, restlessness/agitation, and impaired concentration, thus resembling that of a major depressive disorder (MDD) experienced at other times in adulthood. PPD is often comorbid with anxiety [6,7], and is strongly predicted by a prepartum history of either depression or anxiety [2][3][4][5] (Box 1). While it is unclear whether PPD has any unique symptom characteristics [2,3], both postpartum anxiety and depression are obviously unique in their timing, some of their physiological and psychosocial risk factors (Box 2), and their consequences for the mother-infant dyad if not the entire family unit [4][5][6].…”
Section: Postpartum Anxiety and Depression Occur In At Least 1 In mentioning
confidence: 99%
“…PPD is often comorbid with anxiety [6,7], and is strongly predicted by a prepartum history of either depression or anxiety [2][3][4][5] (Box 1). While it is unclear whether PPD has any unique symptom characteristics [2,3], both postpartum anxiety and depression are obviously unique in their timing, some of their physiological and psychosocial risk factors (Box 2), and their consequences for the mother-infant dyad if not the entire family unit [4][5][6]. Precise rates of postpartum anxiety and depressive disorders are very difficult to ascertain due to the heterogeneity of the disorders, differences among studies in their research populations, the many diagnostic tools and criteria used for their diagnosis, and an overall lack of screening for psychiatric symptoms in postpartum women [7][8][9].…”
Section: Postpartum Anxiety and Depression Occur In At Least 1 In mentioning
confidence: 99%
“…Previous studies have indicated that there exists a relationship between physio-somatic symptoms and depression in pregnant women (Fairbrother, Hutton, Stoll, Hall, & Kluka, 2008;Mellor, Chua, & Boyce, 2014;Skouteris et al, 2009;Tomfohr, Buliga, Letourneau, Campbell, & Giesbrecht, 2015). Several studies have noted that it is difficult to determine the mechanisms underlying perinatal psychiatric illness (Di Florio & Meltzer-Brody, 2015;Jones, Cantwell, & Psychiatrists, 2010). However, other studies have suggested that prenatal depression and physio-somatic symptoms have an immune-inflammatory pathophysiology (Roomruangwong, Kanchanatawan, Sirivichayakul, Mahieu, et al, 2017).…”
Section: Heterogeneity Of Clinical Phenotypes Of Perinatal Depressimentioning
confidence: 99%
“…Our understanding of the etiology of postpartum depression (PPD), defined as moderate to severe depression in a mother following childbirth, continues to evolve with evidence suggesting that PPD may be mechanistically distinct from depression occurring in the non-pregnant state in a woman’s life (Di Florio and Meltzer-Brody 2015; Pawluski et al 2017). Moreover, symptom features may differ between PPD and depression outside the peripartum period (Hoertel et al 2015).…”
Section: Introductionmentioning
confidence: 99%